Metacognitive awareness and reading comprehension in a pro-CLIL university setting - Pereira Rojas, Silvia Inés (Íkala, Revista de Lenguaje y Cultura, 2015)
This study explores the situation of a group of Business Administration students in a pro-CLIL context at Complutense University of Madrid. Two independent but complementary studies were conducted. Study 1 is a questionnaire on students’ perception of their use of metacognitive strategies when reading financial accounting texts in English. Study 2 explores students’ performance when completing a multidisciplinary reading and writing task. The data collected through a questionnaire was contrasted with the results students obtained in a tailor-made task. Results show that to a certain extent there is a link among both studies with respect to student`s perceived use of reading strategies and their actual performance regarding metacognitive awareness. Although participants could perfectly deal with the assessment from both perspectives: language and content, some weakness could be observed when the students had to manage critical reading skills such as justifying, deducing and inferring. These partial results could represent a contribution to those university contexts where official bilingual degrees are being implemented.